Decoy oligodeoxynucleotide technology: an emerging paradigm for breast cancer treatment. Issue 1 (January 2020) - Tehran, Maryam Mahjoubin; Rezaei, Samaneh; Jalili, Amin; Aghaee-Bakhtiari, Seyed Hamid; Sahebkar, Amirhossein
Highlights: Breast cancer is the most common cancer in women worldwide. There is an urgent need to identify new therapies for incurable breast cancer patients. Decoy oligodeoxynucleotide interference with the expression of target genes. We present the state-of-the-art on the use of decoys against breast cancer. Abstract : Breast cancer is the most common cancer in women worldwide. Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer, which is resistant to conventional therapies. Therefore, there is an urgent need to identify new therapies for treating incurable breast cancer in patients. Decoy oligodeoxynucleotides (ODNs) are synthetic oligonucleotides that have a high affinity for a specific transcription factor and can be transfected into target cells to bind to their respective target and alter gene transcription. With these powerful tools available, it is highly possible to effectively regulate the expression of genes that are involved in the pathogenesis of breast cancer. Here, we highlight the studies using decoy ODNs for the development of novel therapies against breast cancer.